The Impact of Leader–Member Relationships on Team Effectiveness Through Speaking Up and Silence: A Cross-Sectional Study in Rural Chinese Hospitals - Wang H; Buljac-Samardzic M; van Wijngaarden JDH; van de Klundert J (Journal of Healthcare Leadership)
Hujie Wang,1 Martina Buljac-Samardzic,1 Jeroen David Hendrikus van Wijngaarden,1 Joris van de Klundert1,2 1Erasmus School of Health Policy & Management, Erasmus University Rotterdam, Rotterdam, the Netherlands; 2School of Business, Universidad Adolfo Ibáñez, Santiago, ChileCorrespondence: Hujie Wang, Erasmus School of Health Policy & Management, Erasmus University Rotterdam, Burgemeester Oudlaan 50, Rotterdam, 3062PA, the Netherlands, Email wang@eshpm.eur.nlIntroduction: Although the importance of leader–member relationships in teamwork is acknowledged in literature, a deeper understanding of this relationship is lacking, especially in rural areas. The impact of leader–member relationships on team outcomes is especially important in rural Chinese hospitals as improving teamwork forms a national health reform priority in these hospitals. This study investigates how leader-member relationships (ie leader-member perceived similarity and power distance orientation) influence team outcomes (ie perceived quality of care and job satisfaction) via speaking up and silence.Methods: An online questionnaire was completed by 1017 team members (ie doctors, nurses and other healthcare professionals) of 300 teams in four rural Chinese hospitals in October 2022. The questionnaire measured leader-member perceived similarity, power distance orientation, speaking up, silence, perceived quality of care, job satisfaction and control variables. Multilevel mediation analysis was conducted to test the hypotheses.Results: Leader–member perceived similarity and power distance orientation are positively related to speaking up (β=0.61, p< 0.01; β=0.17, p< 0.01 respectively) and to silence (β=0.41, p< 0.01; β=0.63, p< 0.01 respectively). Speaking up is positively related to the perceived quality of care (β=0.24, p< 0.01; β=0.46, p< 0.01) and job satisfaction (β=0.30, p< 0.01; β=0.54, p< 0.01), while the impact of silence is not significant. Finally, speaking up mediates the associations of both leader-member perceived similarity and power distance orientation with perceived quality of care (β=0.15, p< 0.01; β=0.08, p< 0.01 respectively) and job satisfaction (β=0.30, p< 0.01; β=0.54, p< 0.01 respectively).Conclusion: Speaking up, rather than silence, contributes to team functioning by mediating the impact of leader–member relationships to team outcomes. Hospital management may therefore seek to stimulate speaking up by focussing on leader-member relationships: increasing leader-member similarity and promoting members’ power distance orientation. However, any unintended effect of increased silence through these leader–member relationships is an important area of future research, which can adopt multidimensional models of speaking up and silence.Keywords: leader-member relationship, leader-member perceived similarity, power distance orientation, speaking up, silence